The Neural Signature of Syntactic Processing - Castillo, Concha (Complutense Journal of English Studies, 2017)
The aim of this paper is to contribute to the understanding about the processing of syntax in the brain and/or mind of speakers. The focus is specifically on the neural signature of the processing of tense features and of agreement features on the one hand, and on the neural signature of the stage that argua-bly antecedes the processing of tense features and of agreement features on the other. Neuroimaging studies of the last two decades or so have come to establish that parts of the left inferior frontal gyrus (LIFG) are responsible for syntactic computing proper, and that the left posterior middle/superior tem-poral gyrus (MTG/STG) appear to be in charge of the projection of phrase structure. Based upon such findings, I defend the convenience of establishing specific goals or tasks that can contribute to their refinement, and that can lead to the acknowledgment of the topography and timing of neural activity at the very first stages of the processing of a sentence.